A Comparative Analysis of Self-Report and Psychophysiological Measures of Emotion in the Context of Tourism Advertising. (November 2018) - Li, Shanshi; Walters, Gabby; Packer, Jan; Scott, Noel
This study investigates the influence of emotional responses evoked by destination television advertisements on three common variables of interest when assessing tourism advertising effectiveness: attitude toward the advertisement, postexposure destination attitude and visit intention. In particular, this study used a combination of self-report and psychophysiological measures of emotion and explored the consistency between these two measurement techniques. A total of 101 participants were exposed to 18 existing destination commercials while their real-time psychophysiological responses and self-report data were collected. The results show that the influence of ad-evoked emotions on tourism advertising effectiveness varied according to the way emotion was measured. The effects of pleasure on tourism advertising effectiveness were much weaker when pleasure was measured physiologically than when self-report measures were used. Physiological arousal, however, was not found to be a significant indicator of advertising effectiveness. The results highlight the importance of valid and reliable measurement of emotion and raise concern over the possible overestimation of the relationship between self-reported emotional responses and advertising effectiveness.